Determination of Land Boundaries in the Jurisprudence of the International Court of Justice - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
This paper deals with several territorial disputes, regarding the land delimitation, which were put before the International Court of Justice. The determination of international borders is one of the most important questions of international law an the International Court of Justice represents a very important judicial instance to which states can address if they have an unsolved boundary question with the neighbouring states. In the territorial disputes at the Court State Parties were not only states that were formed in the process of decolonisation but also some European states such as, for example, The Netherlands and Belgium. The principles that Court has applied in the process of dispute resolution were different regarding the region and demands of the State Parties. The Court should, firstly, apply international law that means sources envisaged in the Article 38 of its Statute. In its jurisprudence, it used at the first place international treaties, where that was possible, but also the principle of uti possidetis and the principle of effectivity in order to resolve the dispute presented before him by the Parties.